Structural and Electric Investigations of Al-doped nano Nickel Ferrite - Salam H. Ali Al-Hadad; Shahad Humam Sulaiman (Engineering and Technology Journal, 2015)
Aluminum doped nickel ferrite samples with composition NiFe2-xAlxO4 (where; x=0, 0.2 ,0.4, 0.6, 0.8, 1, 1.2, 1.4), were synthesized by using sol-gel auto combustion method at temperature about 200°C,then pelletized and sintered at different temperatures (900, 1000, 1100 and 1200°C) . The present work focuses on studying the structural and electrical properties of Ni-Al ferrite by using many analysis’s like x-ray diffraction, LCR meter, FTIR and AFM. The results show that the chemical composition has a major effect on electrical, structural, and physical properties. The result also showed that the dielectric constant and dielectric loss decreased with the increase of the Al content in Ni-Al ferrite sintered at 12000C.